Оказіоналізми як джерело збагачення сучасної української літературної мови (на матеріалі романів Є. Пашковського) - Дюндик, О. (Лексикографічний бюлетень, 2012)
The article focuses on recent researches which affirm that there is a tendency to decrease the number of words in different languages, namely in English, Spanish and Hebrew and assume the same tendency in Ukrainian language. According to this problem, very important issue is appearance of new words – neologisms. Its purpose and functions in postmodern literature on the whole and in the novels by Evgen Pashkovsky has been analyzed in the article.